An investigation on adaptive reuse of historical buildings in Malaysia / Tuan Noor Khairunadzrah Tuan Soh - Tuan Soh, Tuan Noor Khairunadzrah (2014)
The dissertation focuses on case studies of Central Market Kuala Lumpur (Pasar Seni Kuala Lumpur), Museum of History and Ethography Malacca (Stadthuys) and Muzium Islam (Islamic Museum), Kelantan. The purpose of this dissertation are to define the meaning of adaptive-reuse and value of conservation historical buildings in Malaysia; to identify the adaptive reuse techniques practice of historical buildings in Malaysia and to recommend the best way of implementing adaptive reuse to historic buildings in Malaysia.